Modeling and experimental investigation of a controllable rotary fluid damper - Cao, X.; Zhou, J.; Yu, M.; Wang, Y. (Archives of Mechanics, 2023)
Controllable rotary fluid damper (CRFD) is an efficient and cheap energy dissipation device, which is used to reduce the impact of vibration in mechanical systems. In this paper, the CRFD controlled by a servo motor is developed to reduce the effects of vibrations in the helicopter flight control system. The dynamic mechanical characteristic of the CRFD is experimentally investigated by the MTS machine. Due to the complex factors such as high shear thinning rate and compressibility of the damping medium, inertia of moving parts and internal friction, the CRFD studied has highly nonlinear hysteresis characteristics. The accuracy of the damper modeling is of great significance for designing effective vibration reduction methods. Therefore, a new generalized viscous–nonlinear elastic model is proposed to track the mechanical characteristics of CRFD. On the basis of parameter sensitivity analysis, the proposed generalized viscous–nonlinear elastic model is modified. According to the identification results of the modified model, the main parameters are fitted as polynomial functions of motor rotation angle. Through error analysis between analytical torques and experimental torques, it is concluded that the modified generalized viscous–nonlinear elastic model has the smallest error compared with Kwok and Maxwell models, which indicates that the proposed modified model can accurately describe the mechanical characteristics of the CRFD under different working conditions.